What enables or prevents women with depressive symptoms seeking help in the postnatal period?. (2nd April 2019) - Newman, Tabitha Claire; Hirst, Janet; Darwin, Zoe
Abstract : Background: Perinatal mental health problems affect approximately 20% of women. The most common condition is postnatal depression; however, many women do not seek help. Aims: To identify and synthesise evidence on factors that enable or prevent help-seeking in women with depressive symptoms in the postnatal period. Methods: A qualitative systematic review was conducted using electronic databases and pre-determined eligibility criteria. Findings: Thematic synthesis of the included studies ( n =4) identified the following themes: the influence of healthcare services, the influence of others and the influence of women themselves. Help-seeking was shaped by women's ability to recognise their symptoms, the reactions (experienced or anticipated) of others and the organisation of services. Conclusion: An improved interface between maternity and mental health services and enhanced health professional interactions are needed. However, meaningful change may require empowering women's self-assessment and public health messages to improve understanding of postnatal depression.